Problems Experienced by Adolescents with Autism Spectrum Disorder: Exploring Social, Educational and Economic Variables - Saeb K. El Lala; Ola M. Abusukkar (Space and Culture, India, 2020)
The study investigates the problems of adolescents with Autism Spectrum Disorder (ASD) from the perspective of ASD specialists and adolescent’s families. It comprises of 228 ASD specialists and 294 families of ASD adolescents. The sample represents all areas of the Kingdom of Saudi Arabia (henceforth – KSA): north, south, east, west and centre. Variables of the study are adolescents’ gender, age, residential area, as well as the qualification of ASD specialists and family members. To accomplish the study, the researchers designed a questionnaire that includes variables regarding six significant problems: Educational, Recreational, Economic, Health, Psychological, and Social. The results reveal that families rate the economic problems higher than average, while the recreational ones – lower; specialists rate economic problems higher than average and educational ones – the lowest. As for gender variable, specialists and families note the differences in favour of females; for age variable, specialists and families note that 15-18 years old ASD adolescents have more problems. The results show that qualification of specialists as well as family members is of significant relevance in relation to ASD adolescents. Both specialists and family members are mostly from the central regions.